1
$\begingroup$

Given that $\lim_{n\rightarrow\infty}n\left(\frac{b_n}{b_{n+1}}-1\right)=\lambda>0$, show that $\sum_{n=1}^{\infty}{\left(-1\right)^{n}b_{n}}\left(b_{n}>0\right) $ converges.

Using the definition of limit of sequence, I can prove that $\left\{b_n\right\}$ is monotonically decreasing when $n$ is large enough. But how to prove $\lim_{n\rightarrow\infty}b_n=0$?

$\endgroup$
  • $\begingroup$ The sequence is bounded below and decreasing. Now assume it didn't converge to $0$. What can you say then about $\lim_{n\to\infty}n\left(\frac{b_n}{b_{n+1}}-1\right)$? $\endgroup$ – martin.koeberl Mar 29 '17 at 2:24
  • $\begingroup$ @martin.koeberl Then it has a nonzero and positive limit (which is impossible?). But I don't know how to prove it by absurd. $\endgroup$ – pjpj Mar 29 '17 at 2:26
  • $\begingroup$ I don't think it is trivial. If $b_n$ converges to a limit greater than zero, $\frac {b_n}{b_{n+1}}-1$ converges to zero. Certainly without the factor $n$ you couldn't claim that $b_n \to 0$ $\endgroup$ – Ross Millikan Mar 29 '17 at 2:45
  • $\begingroup$ Now, you have to use the definition of convergence in various ways. The keypoints being that above limit stays above $\lambda-\frac{\epsilon}2$ for any $\epsilon$ you choose (from some point), and that you can write $\frac{b_n}{b_{n+1}}-1=\frac{b_n-b_{n+1}}{b_{n+1}}$. For the numerator, use the definition of convergence, for the denominator, use that the limit is assumed to be strictly bigger than $0$. $\endgroup$ – martin.koeberl Mar 29 '17 at 2:46
  • $\begingroup$ @martin.koeberl Why is it above $\lambda-\frac{\epsilon}{2}$? $\endgroup$ – pjpj Mar 29 '17 at 3:10
2
$\begingroup$

Given $0 < r < \lambda$, there exists $N$ such that if $n \geqslant N$ we have

$$n \left(\frac{b_n}{b_{n+1}}-1 \right)> r \\ \implies \frac{b_n}{b_{n+1}} > 1 + \frac{r}{n}.$$

Hence for all $m > N$ it follows that

$$\frac{b_N}{b_m} > \prod_{k=N}^{m-1}\left(1 + \frac{r}{k} \right).$$

The infinite product on the RHS diverges to $+ \infty$ as $ m \to \infty$ since $\sum 1/k $ diverges. Therefore, $b_m$ converges to $0$.

$\endgroup$
0
$\begingroup$

If $\lim_{n\rightarrow\infty}n\left(\frac{b_n}{b_{n+1}}-1\right) =c>0 $, then, arguing loosely, $\frac{b_n}{b_{n+1}}-1 \approx c$ so $\frac{b_n}{b_{n+1}} \approx 1+c$.

Therefore, for any $0 < d < c$, for all large enough $n$, $\frac{b_n}{b_{n+1}} \ge 1+d$.

By induction, $\frac{b_n}{b_{n+k}} \ge (1+d)^k$ or $b_{n+k} \le \frac{b_n}{(1+d)^k} \to 0$ as $k \to \infty$.

Therefore $\lim_{n \to \infty} b_n = 0$.

Since $\frac{b_{n+1}}{b_n} \le \frac1{1+d}$ for all large enough $n$, $b_n$ is a decreasing sequence for large enough $n$.

By the alternating series theorem (alternating sign, limit zero, decreasing), the sum converges.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.